The Implications of Marriage Structure for Men's Workplace Attitudes, Beliefs, and Behaviors toward Women. (June 2014) - Desai, Sreedhari D.; Chugh, Dolly; Brief, Arthur P.
Based on five studies with a total of 993 married, heterosexual male participants, we found that marriage structure has important implications for attitudes, beliefs, and behaviors related to gender among heterosexual married men in the workplace. Specifically, men in traditional marriages—married to women who are not employed—disfavor women in the workplace and are more likely than the average of all married men to make decisions that prevent the advancement of qualified women. Results show that employed men in traditional marriages tend to (a) view the presence of women in the workplace unfavorably, (b) perceive that organizations with higher numbers of female employees are operating less smoothly, (c) perceive organizations with female leaders as relatively unattractive, and (d) deny qualified female employees opportunities for promotions more frequently than do other married male employees. Moreover, our final study suggests that men who are single and then marry women who are not employed may change their attitudes toward women in the workplace, becoming less positive. The consistent pattern of results across multiple studies employing multiple methods (lab, longitudinal, archival) and samples (U.S., U.K., undergraduates, managers) demonstrates the robustness of our findings that the structure of a man's marriage influences his gender ideology in the workplace, presenting an important challenge to workplace egalitarianism.